Artistic orientation, financial literacy and entrepreneurial performance. Issue 1 (31st May 2019) - Purnomo, Boyke Rudy
Abstract : Purpose: This study aims to examine the relationship between artistic orientation and entrepreneurial performance and how other central entrepreneurial resources, namely, entrepreneurial orientation and financial literacy, affect this relationship. Design/methodology/approach: Regulatory focus theory was used to develop the model. A survey of 375 small creative business entrepreneurs was conducted in Yogyakarta, Indonesia, and a hierarchical linear regression was used for data analysis. Findings: The results reveal a positive correlation between artistic orientation, entrepreneurial orientation, financial literacy and entrepreneurial performance. Therefore, artistic orientation affects a creative firm's financial and nonfinancial performance. In addition, artistic orientation and financial literacy provide a positive influence on the overall performance of a creative venture. However, the interaction effect of entrepreneurial orientation and financial literacy on the artistic orientation – performance relationship – is invisible Practical implications: This research provides guidance on how creative firms may focus on the acquisition, development and protection of useful resources, namely, artistic orientation and financial literacy Originality/value: This research is the first systematic empirical test evaluating the relationship between artistic orientation and entrepreneurial performance